Complete hydatidiform mole with a coexisting foetus of term pregnancy: a case report and review of the literature - Jiang, Lin; Xi, Fangfang; Luo, Qiong (Journal of the Pakistan Medical Association, 2022)
A case of a complete mole with a full term live foetus misdiagnosed as placental mesenchymal dysplasia prenatally is being reported here. The infant was delivered at term, and the placenta was accompanied with molar changes. Both the mother and baby were healthy with no complications at one-year follow-up. This report systematically summarises identification methods to reduce the rate of misdiagnosis for better pregnancy outcomes. Keywords: Complete hydatidiform mole; Twin pregnancy; Placental mesenchymal dysplasia; Gestational trophoblastic neoplasia.